2000
DOI: 10.1111/j.1745-7599.2000.tb00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation Intervention in a Nurse Practitioner Managed Clinic

Abstract: Tobacco cessation counseling by health care professionals has been associated with increased tobacco cessation rates. In this study we compare the effectiveness of two smoking cessation approaches administered by nurse practitioners--a stepped care approach (n = 34) and a routine care approach (n = 41), using a pre- and post-test control group study design. Additionally, this study was guided by the "stages of change" construct of the transtheoretical model. Study results indicated that nurse practitioners del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It may be that the NPs actually advised quitting s m o h g much more frequently; however, documentation did not support this. Moreover, the NP findings might have been more accurate had the study protocols indicated a direct questioning of patients, as was the case in the Reeves et al (2000) study. Follow-up plans include interventions in each center with staff and NPs to increase awareness regarding smoking advice and documentation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It may be that the NPs actually advised quitting s m o h g much more frequently; however, documentation did not support this. Moreover, the NP findings might have been more accurate had the study protocols indicated a direct questioning of patients, as was the case in the Reeves et al (2000) study. Follow-up plans include interventions in each center with staff and NPs to increase awareness regarding smoking advice and documentation.…”
Section: Discussionmentioning
confidence: 95%
“…Counseling by healthcare providers, who are viewed as authorities, can facilitate changes in smoking behaviors (Agency for Health Care Policy and Research, 1996). Few studies of NP effectiveness in smoking cessation exist (Pohl & Caplan, 1998;Reeves, Calabro, & Adams-McNeill, 2000;Rice et al, 1994). The majority of research has been focused on NPs' perceptions of the implementation of smoking cessation advice to their patients (Block, Hutton, & Johnson, 2000;Neely, 2000).…”
Section: Care and Nurse-managed Centersmentioning
confidence: 99%
“…In the one remaining study, the stage of change was not identified during assessment or evaluation phases, however an intervention plan was formulated using other TTM concepts rather than stage of change. There were six studies comparing the outcome of the stage-matched intervention with that of no stage-matched intervention [28][29][30][31][32][33]. Findings from all of the studies except one [28] showed that the stage-matched intervention is more effective than no stage-matched intervention.…”
Section: Use Of Stage-matched Interventionmentioning
confidence: 98%
“…It is well documented that nurses are effective in delivering tobacco cessation interventions in a variety of patient care settings (Andrews, Tingen, & Harper, 1999;Gebauer, Kwo, Haynes, & Wewers, 1998;Hollis, Lichenstein, Vogt, Stevens, & Biglan, 1993;Stanislaw, & Wewers, 1994;Taylor, Houston-Miller, Killen, & DeBusk, 1990;Reeve, Calabro, &Adams-McNeill, 2000). In recent years, nurses have demonstrated increased efficacy with smoking cessation interventions for hospital inpatients with cardiovascular disease (Allen, 1996;DeBusk et al, 1994;Graham-Garcia, & Heath, 2000;Rice, 1999).…”
Section: Nurses' Tobacco Cessation Practicesmentioning
confidence: 99%
“…In recent years, nurses have demonstrated increased efficacy with smoking cessation interventions for hospital inpatients with cardiovascular disease (Allen, 1996;DeBusk et al, 1994;Graham-Garcia, & Heath, 2000;Rice, 1999). In ambulatory care settings, nurse practitioner (NP) managed clinics have been established to provide intensive smoking cessation interventions with increased cessation rates (Andrews, Tingen, & Harper, 1999;Reeve, Calabro, & Adams-McNeill, 2000).…”
Section: Nurses' Tobacco Cessation Practicesmentioning
confidence: 99%